The impact of a global service-learning immersion experience on the efficacy of caring and professional nurse values development among nursing students in the US and Portugal: A mixed methods study - Kerry A. Richardson; Maryellen D. Brisbois; Mary K. McCurry; DM Leone-Sheehan (Journal of Nursing Education and Practice, 2026)
Background and objective: Caring is a core value in nursing. Nurse educators play a vital role in cultivating caring attributes and professional values in baccalaureate students through innovative pedagogies such as global service-learning. Developing caring behaviors and professional values may improve patient care, nurse satisfaction, and retention. The objective of this study was to explore the impact of a global service-learning immersion experience on the caring efficacy and professional nursing values among junior nursing students in the United States and Portugal. Methods: An explanatory sequential mixed methods study was conducted with junior nursing students from the United States and Portugal (n = 21). The Caring Efficacy Scale (CES) and the Nurses Professional Values Scale-Three (NPVS-3) were administered pre-and post-immersion, with one open-ended reflection question post exchange. Data were analyzed using SPSS version 30.0 with descriptive and inferential statistics, thematic analysis, and integration of quantitative and qualitative findings. Results: A statistically significant increase was found in Caring Efficacy Scale post score (p = .045). The NPVS-3 total post score was not statistically significant; however, mean scores increased from 114.44 (SD = 15.78) to 118.94 (SD = 9.46). The NPVS-3 Caring Factor (p < .001) and Professionalism Factor (p = .040) showed statistically significant improvement post exchange. Mixed methods integration demonstrated strong convergence through a central theme of Transformative Experience. Conclusions: Participation in a global service-learning immersion fostered meaningful transformation in students’ perspectives and strengthened understanding of caring and professional nursing values. Integration of qualitative findings with improvements in Caring Efficacy and NPVS-3 Caring and Professionalism factor scores demonstrated a strong theory-to-practice connection aligned with Watson’s Theory of Human Caring and Mezirow’s Transformative Learning Theory. These findings support global service-learning immersion as a valuable strategy for promoting compassionate, ethical, patient-centered, globally informed nursing practice.